2009
DOI: 10.1080/18146620902857558
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of policies and programmes related to children with disabilities in Botswana

Abstract: Globally, most children with disabilities are neglected by society. Research shows that the majority of the world's 450 million people with disabilities are found in developing countries Knutson, 1998 and2000). This study seeks to: (a) identify available programmes of education and policies that are aimed at helping children with disabilities in schools; (b) determine the nature of services that are available to disabled children in schools; and (c) determine some strategies that the government and society can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The findings of these studies reported that services received by IWDs did not address their problems adequately and a large number of IWDs were disgruntled about the overall services that they receive (Tebogo, 2013). The challenges in offering quality services are many, with one of them being a lack of exact data on the disability population (Shumba & Taukobong, 2009). In addition, the issues of disability are mostly left to nongovernmental organizations (NGOs) to address, with the government having little to no stake (Pfumorodze & Fombad, 2011).…”
Section: History Of Disability Movement In Botswanamentioning
confidence: 99%
“…The findings of these studies reported that services received by IWDs did not address their problems adequately and a large number of IWDs were disgruntled about the overall services that they receive (Tebogo, 2013). The challenges in offering quality services are many, with one of them being a lack of exact data on the disability population (Shumba & Taukobong, 2009). In addition, the issues of disability are mostly left to nongovernmental organizations (NGOs) to address, with the government having little to no stake (Pfumorodze & Fombad, 2011).…”
Section: History Of Disability Movement In Botswanamentioning
confidence: 99%
“…There is no up-to-date database that provides this information and there are only a few studies that have been conducted relating to people with disabilities in Botswana in the past decade (Chhabra, Srivastava, & Srivastava, 2009;Grol, 2000;Shumba & Taukobong, 2009;Tsheko, 2007). There is no up-to-date database that provides this information and there are only a few studies that have been conducted relating to people with disabilities in Botswana in the past decade (Chhabra, Srivastava, & Srivastava, 2009;Grol, 2000;Shumba & Taukobong, 2009;Tsheko, 2007).…”
Section: Introductionmentioning
confidence: 99%